2000
DOI: 10.1007/s002470050749
|View full text |Cite
|
Sign up to set email alerts
|

Cranial MRI in neonatal hypernatraemic dehydration

Abstract: Severe neonatal hypernatraemia is a life-threatening electrolyte disorder because of its neurological complications. These are brain oedema, intracranial haemorrhages, haemorrhagic infarcts and thromboses. There are few reports concerning the radiological findings in the central nervous system in severe neonatal hypernatraemia. Cranial MRI findings in hypernatraemia have been reported in an older child, but have not been described in newborn infants. We report the cranial MRI findings in a newborn infant with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…However, inadequate breastfeeding may result in significant weight loss and hypernatremic dehydration (5-15), a potentially lethal condition that can be associated with severe complications (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…However, inadequate breastfeeding may result in significant weight loss and hypernatremic dehydration (5-15), a potentially lethal condition that can be associated with severe complications (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Hypernatremic dehydration is assumed to be a rare complication of breastfeeding, 7 but recent reports have suggested that the incidence is increasing. [8][9][10][11] The failure to diagnose hypernatremic dehydration can have serious consequences, including seizures, intracranial hemorrhage, 12 vascular thrombosis, 13 and death. 14,15 The purpose of this study was to assess the incidence and complications of breastfeeding-associated hypernatremia among hospitalized neonates at a large pediatric tertiary care center in the United States.…”
mentioning
confidence: 99%
“…Acute CNS dysfunctions as well as permanent CNS sequelae are seen in most infants and children with a serum sodium concentration of more than 158 mmol/l and clinical symptoms correlate with the level of the serum sodium concentration [5] . The overall mortality of severe hypernatremia (Na + levels 1 160 mmol/l) is described in the range of 10% [4,5] .…”
Section: Discussionmentioning
confidence: 99%
“…Brain hemorrhage, either massive hemorrhage or multiple small hemorrhages and thromboses, may occur when hypernatremia causes cellular dehydration with resultant brain shrinkage and tearing of cerebral vessels [4,5] . Acute CNS dysfunctions as well as permanent CNS sequelae are seen in most infants and children with a serum sodium concentration of more than 158 mmol/l and clinical symptoms correlate with the level of the serum sodium concentration [5] . The overall mortality of severe hypernatremia (Na + levels 1 160 mmol/l) is described in the range of 10% [4,5] .…”
Section: Discussionmentioning
confidence: 99%